Save a Place for Leadership in the Debate on Adequacy: A New Model for Developing Leadership for Schools - Mary Devin (Educational Considerations, 2004)
In the midst of discussions on adequacy of funding, schools are being held accountable for the success of all students and for raising student performance to the highest level ever.